Carbon stable isotopes as indicators of coastal eutrophication. Issue 3 (1st April 2014) - Oczkowski, Autumn; Markham, Erin; Hanson, Alana; Wigand, Cathleen
Abstract : Coastal ecologists and managers have frequently used nitrogen stable isotopes (δ 15 N) to trace and monitor sources of anthropogenic nitrogen (N) in coastal ecosystems. However, the interpretation of δ 15 N data can often be challenging, as the isotope values fractionate substantially due to preferential retention and uptake by biota. There is a growing body of evidence that carbon isotopes may be a useful alternative indicator for eutrophication, as they may be sensitive to changes in primary production that result from anthropogenic nutrient inputs. We provide three examples of systems where δ 13 C values sensitively track phytoplankton production. First, earlier (1980s) mesocosm work established positive relationships between δ 13 C and dissolved inorganic nitrogen and dissolved silica concentrations. Consistent with these findings, a contemporary mesocosm experiment designed to replicate a temperate intertidal salt marsh environment also demonstrated that the system receiving supplementary nutrient additions had higher nutrient concentrations, higher chlorophyll concentrations, and higher δ 13 C values. This trend was particularly pronounced during the growing season, with differences less evident during senescence. And finally, these results were replicated in the open waters of Narragansett Bay, Rhode Island, USA, during a spring phytoplankton bloom. These three examples, taken together with the pre‐existing body of literature, suggest that, at least in autotrophic, phytoplankton‐dominated systems, δ 13 C values can be a useful and sensitive indicator of eutrophication.